The Development of Worksheet Based on Google My Maps Web Application to Attain Basic Competencies in High School Geography Learning - Ismail, Jalu Rafli; Nandi, Nandi; Ridwana, Riki (Universitas Negeri Surabaya, 2023)
This research was carried to develop and test Web-GIS worksheet to attain basic competences in geography learning as researched in Class XI IPS in SMAK 3 Bina Bakti Bandung. This research implemented 4D model. The instruments that were used are expert appraisal sheet through the validation of aspect of media and content, percentage of practicality, student performance test, and response questionnaire. The result of this study is the Web-GIS worksheet that is able to be implemented tp support the attainment of Basic Competencies 3.6 and 4.6. Validity of worksheet is indicated by content validity of 91.66% and media validity of 92.5%. Worksheet practicality is proven by 93.75% implementation percentage with students’ performance score as many as 87.83%. Through response questionnaire, there are as many as 88.98% positive responses toward worksheet’s didactic, constructive, and technical requirements, together with basic competencies attainment indicators. Findings from this research indicate that the developed Web-GIS worksheet is valid and practically able to be implemented in geography learning to attain basic competencies of local culture mapping. Keywords: Geography learning, Worksheet, Web-GIS